Hubungan Antara Perubahan TitiK B Anterior (BA) dengan Berat Badan Lahir Bayi pada Persalinan Normal - Beny Gunawan; Ermawati Ermawati (Universitas Andalas, 2020)
Background : Pelvic organ prolapse (POP), also known as urogenital prolapse, is a decrease in pelvic organs which causes protrusion of the vagina, uterus or both. Determination of POP is seen from anterior vaginal wall prolapse (cystocele), uteri (urethrocele) and posterior vaginal wall (rectocele). In identifying the incidence of POP can be seen by knowing anatomic abnormalities, especially cytoceles, based on the degree measured by the Prevalence Organ Prolapse Quantification (POPQ) system. In the cystocele the POPQ assessment is focused on the anterior B point (Ba), which is the point that is in the anterior vaginal wall, between the Aa point and the anterior fornix.Objectives : determine the relationship between changes in anterior point B with the birth weight of infants in normal labor. Method: This study was conducted with a cross sectional comparative study method in the obgin polyclinic Prof. dr. Hanafiah Batusangkar from September to December 2017. The number of samples was 74 people with 37 people in the group with an anterior point B change> 3 cm and 37 people in the group with an anterior point B change <3 cm. Data analysis using SPSS version 22, theresults of statistical tests were significant if p <0.05.Results: There was a relationship between age (p = 0.041) and parity (p = 0.047) with changes in anterior B point (BA) in normal labor and women who gave birth to birth weight. 3500 gram babies had 2.7 times the chance to experience changes in anterior B points (BA) of> 3 cm.Conclusion: this study is that there is a relationship between birth weight of babies with anterior point B changes. Keywords: Pelvic Organ Prolap, Prevalence Organ Prolapse Quantification (POPQ), Anterior Point B